Literature for primary school and education of Republican citizen, in the Revista de Ensino (SP-Brazil)-1902-1918 - Do Rosário Longo Mortatti, Maria [UNESP] (FapUNIFESP (SciELO), 2018)
Aiming to contribute to understand unexplored aspects of the history of children's literature, of teaching reading and of education in Brazil, is focused the Section Children's Literature of the Revista de Ensino, edited between 1902 and 1918, by Beneficent Association of Public Teachers of Sao Paulo State. By means of analyzing the configuration of the texts published in this Section, it is concluded that: The translations/adaptations, paraphrases or original texts by Brazilian or foreign authors characterizes a precursor corpus of the Brazilian children's literature and contributed to disseminate a conception of children's literature that oscillates between didactic and literary genre, articulated with the purposes of primary school education under a republican project to the nation.
Literatura para a escola primaria E educacao do cidadao Republicano, na revista de ensino (SP-Brasil)-1902/1918
Keywords: Children's literature; History of children's literature; History of education in Brazil; History of teaching reading; Revista de Ensino